Hypospermia Improvement in Dogs Fed on a Nutraceutical Diet - Francesco Ciribé; Riccardo Panzarella; Maria Carmela Pisu; Alessandro Di Cerbo; Gianandrea Guidetti; Sergio Canello (The Scientific World Journal)
Male dog infertility may represent a serious concern in the canine breeding market. The aim of this clinical evaluation was to test the efficacy of a commercially available nutraceutical diet, enriched with Lepidium meyenii, Tribulus terrestris, L-carnitine, zinc, omega-3 (N-3) fatty acids, beta-carotene, vitamin E, and folic acid, in 28 male dogs suffering from infertility associated with hypospermia. All dogs received the diet over a period of 100 days. At the end of the evaluation period, no adverse effects, including head and tail anomalies percentage onset, were reported. Interestingly, motility percentage, semen volume and concentration, and total number of sperms per ejaculation significantly increased. Further investigations on a wider cohort of dogs might be useful to better correlate the presence of oxytetracycline in pet’s diet and the onset of infertility and clearly assess the action mechanism of an oxytetracycline-free nutraceutical diet.